Photonic crystal fiber with double-layer rings for the transmission of orbital angular momentum - Qi, Xingyu; Lian, Yudong (Frontiers in Physics, 2023)
In this paper, we propose a novel photonic crystal fiber (PCF) with double-layer rings for transmitting orbital angular momentum (OAM). The substrate of PCF is a pure silicon base. The inner circle is doped with Fluoride to reduce the refractive index (RI), and the transmission domain is doped with Germanium dioxide to increase the RI. On the outer side of the transmission ring, air holes are regularly arranged to restrict the beam transmission within the transmission layer. After calculation, the proposed OAM fiber can effectively support 118 OAM modes in the range of 1.3 1.75 μm with excellent characteristics. In addition, we also found that proposed fiber has "bandgap-like" mode field characteristics.